Way of life: students' motivation towards learning the Quran and Hadith in Malaysia - Wan Mokhtar, Wan Khairul Aiman; Wan Khairuldin, Wan Mohd Khairul Firdaus; Embong, Abdul Hanis; Md Rami, Ahmad Aizuddin; Jalil, Mohammad Syukri; Athiyallah, Arina (Transnational Press London Ltd, 2024)
The motivation of students in studying the Quran and Hadith is crucial for their active involvement and comprehension of these fundamental writings in Islam. Nevertheless, there is a significant deficiency of study about the determinants of motivation, specifically within the educational framework of Malaysia. This study seeks to examine the motivation levels of university students in Malaysia in regards to their interest in learning the Quran and Hadith. The study specifically focuses on exploring potential disparities in motivation levels between genders. Utilising well-established motivational theories, a research methodology based on surveys will be used to evaluate several elements that impact motivation, such as personal interest, religious conviction, perceived relevance, and perceived competence. A total of 427 questionnaires will be electronically delivered to students from various educational levels and backgrounds using random sampling. This method will guarantee the confidentiality and anonymity of the responses. The data analysis will encompass reliability testing, descriptive analysis, and T-tests to investigate gender disparities, utilising the SPSS 2.6 programme. The findings suggest that university students exhibit elevated levels of motivation, and there are no notable disparities between male and female students.